Educational Leadership and Cognitive Change: A Transdisciplinary (Education, Cognitive Psychology, Neuroscience) Model - Meyer, John (Journal of Organizational Psychology, 2021)
This study addressed the complex issues surrounding cognitive change in educators. It analyzed qualitative data gathered from an online Experiential Simulation© (ES©). ES© (Brunner, 2002) uses synchronous chats and written reflections to prompt cognitive dissonance around areas of power and identity. Research data was iteratively compared with education, cognitive psychology, and neuroscience literature to build a model of educator cognitive change. The model explains factors required for individual cognitive change and provides leaders with a model to diagnose barriers and remediate them.